Effect of firing time and wall thickness on the biaxial flexural strength of 3D-printed zirconia - Rues, Stefan; Herpel, Christopher; Ilani, Ali; Schmitt, Clemens; Rammelsberg, Peter; Schwindling, Franz Sebastian (Dental materials, 2024)
Objectives - To evaluate the effect of accelerated firing on 3D-printed zirconia. - Methods - To check if formulae provided by ISO 6872 can be extended to thin samples, finite element analyses were carried out in advance of fabricating 3-mol% yttria-stabilized tetragonal zirconia polycrystal discs by milling and by 3D-printing. Four groups (n = 38 each) of 3D-printed specimens were produced with two nominal thicknesses (0.6 mm and 1.2 mm) and two firing strategies (long: 51 h, accelerated: 14.5 h). In the milled group (thickness 1.2 mm, n = 30), a standard firing program (9.8 h) was selected. Biaxial flexural strength tests were applied and mean strength, characteristic strength, and Weibull modulus were calculated for each group. Differences were analyzed using Welch ANOVA and Dunnett-T3 post-hoc tests. - Results - Maximum tensile stresses occurring during biaxial strength testing can be calculated according to ISO 6872 for thin samples with b > 0.3 mm. Variability of measured strengths values was smaller for milled zirconia compared with 3D-printed zirconia. The 1.2-mm-thick 3D-printed samples had significantly decreased strength after accelerated firing than after long firing. However, for the 0.6-mm-thick samples, comparable mean biaxial strength values of about 1000 MPa were measured for both firing protocols. - Significance - At the moment, long fabrication time for zirconia restorations is a major drawback of 3D-printing when compared with milling technology. This investigation showed that the strength of 0.6-mm-thick zirconia discs fabricated by 3D-printing was not impaired by accelerated firing. Thus, overnight firing of thin-walled 3D-printed zirconia restorations could be possible.
Gesehen am 06.09.2024